2011
DOI: 10.1016/j.jmps.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Elastic reciprocity and symmetry constraints on the stress field due to a surface-parallel distribution of dislocations

Abstract: Elastic reciprocity and geometric symmetry are used to constrain the expressions for stresses due to introduction of line dislocations near a half-space surface. Specifically, a relationship is shown to exist between the changes induced by dislocations of orthogonal Burgers vectors (normal and parallel to the free surface). These results are used to address inconsistencies of solutions in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Taking v ≡ x − ξ , the kernals are [e.g., Head , 1953] k1(v)v4h2+v2+8h2vtrue(4h2+v2true)2+4h2v348h4vtrue(4h2+v2true)3 k2(v)24h3v232h5true(4h2+v2true)3 For a symmetric distribution of slip near the free surface, their contribution is an antisymmetric change in normal stress and a symmetric change in the shear stress. (As summarized by Viesca and Rice [2011], misprints in early reported results for such kernels have unfortunately propagated through the literature. )…”
Section: Rupture Nucleation By Local Increases In Pore Pressurementioning
confidence: 99%
“…Taking v ≡ x − ξ , the kernals are [e.g., Head , 1953] k1(v)v4h2+v2+8h2vtrue(4h2+v2true)2+4h2v348h4vtrue(4h2+v2true)3 k2(v)24h3v232h5true(4h2+v2true)3 For a symmetric distribution of slip near the free surface, their contribution is an antisymmetric change in normal stress and a symmetric change in the shear stress. (As summarized by Viesca and Rice [2011], misprints in early reported results for such kernels have unfortunately propagated through the literature. )…”
Section: Rupture Nucleation By Local Increases In Pore Pressurementioning
confidence: 99%
“…To solve for the crack opening in a manner which solves the elasticity equations in 2D plane strain and meets the traction-free surface boundary conditions at z ¼ H, the numerical integral equation formulation of Erdogan et al [10] (with correction of a misprinted kernel as noted in Ref. [11]) was used, which relates the pressure distribution p(x, t) to the crack opening gap h(x, t) at each time t (with inertia neglected because of the slowness of fracture propagation speeds relative to elastic wave speeds). Also, in view of the low fracture toughness of ice, K Ic % 0.1 MPa, it was judged that toughness became unimportant, in the sense quantified by Garagash and Detournay [12], once crack half-length L(t) was greater than % 10 m. Effectively, over the long length scale of fracture growth (L > 1 km), the problem of fracture becomes asymptotically indistinguishable from the problem of lift-off along a nonadhering (zero K Ic ) interface.…”
Section: Discussionmentioning
confidence: 99%
“…0 þ , the upper side of the fracture plane (i.e., the base of the ice sheet), is given by Erdogan et al [10], although a misprint as identified in Ref. [11] must be corrected. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While the stress r ij11 (r, z; r 0 , z 0 ) due to D rr , deduced from potentials (24) and explicitly given in Appendix C, satisfies the symmetry relation (33), the corresponding stress in Korsunsky (1995) solution does not. Interestingly, Viesca and Rice (2011) also use elastic reciprocity as a means to establish symmetries in dislocation solutions for a half-plane. Actually, with provision for a misprint in the expressions of the potentials, Korsunsky's solution is consistent with the application of the DD derivation rules (22) (Paynter et al, 2007).…”
Section: Discussionmentioning
confidence: 99%